Consumo y costo de medicamentos oncológicos utilizados en cáncer de mama en el servicio de consulta externa adultos del Hospital Edgardo Rebagliati Martins setiembre – diciembre 2007 - Ledesma Carbajal, María Emilia (2008)
In the present work investigation demostrated the consumption and cost of oncologists drug in breast cancer in the service adults external consult of the Edgardo Rebagliati Martins National Hospital during september - december of 2007, for that used the methodology of the Paretos’s law, PDD/100 beds/day, applied to each oncologist drug in studies and finally calculate the cost that these occasions. The results based on the Pareto’s law demonstrated that paclitaxel was the oncologist drug that frecuently was used in september (41 %), october (37 %), november (40 %) and december (50 %), also paclitaxel was the outline of treatment that frecuently was used in september (30.98 %), october (30.81 %), november (33.88 %) and december (38.25 %). About consume the oncologist drug with major consume was paclitaxel with 19.28 PDD/100beds/day. Finally, demostrated that trastuzumab was the most expensive drug and caused a spent of S/. 61617.41, in four months of study, which represents 72.57% of the total expense. However, is necessary the realization of more specific studies than permit characterize better the owner of use of this type of drugs and promote your rational use.